Should I solve it first?

Algebra Level 2

If x + 1 x = 7 x + \frac 1x = 7 , what is the value of x 3 + 1 x 3 x^3 + \frac1{x^3} ?


The answer is 322.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

12 solutions

Chew-Seong Cheong
Jun 12, 2015

Thanks Wendy Natuibs , you are right. I didn't see it earlier.

( x + 1 x ) 3 = x 3 + 3 x + 3 x + 1 x 3 x 3 + 1 x 3 = ( x + 1 x ) 3 3 ( x + 1 x ) = 7 3 3 ( 7 ) = 322 \begin{aligned} \left(x+\frac{1}{x}\right)^3 & = x^3+3x+\frac{3}{x} +\frac{1}{x^3} \\ \Rightarrow x^3 +\frac{1}{x^3} & = \left(x+\frac{1}{x}\right)^3 - 3\left(x+\frac{1}{x}\right) \\ & = 7^3 - 3(7) = \boxed{322} \end{aligned}

Previous Solution \color{#3D99F6}{\text{Previous Solution}}

Using the identities below and substituting a = x a = x and b = 1 x b = \frac{1}{x} , we have:

a 2 + b 2 = ( a + b ) 2 2 a b a 3 + b 3 = ( a + b ) ( a 2 + b 2 a b ) x 2 + 1 x 2 = ( x + 1 x ) 2 2 x ( 1 x ) = 7 2 2 = 47 x 3 + 1 x 3 = ( x + 1 x ) ( x 2 + 1 x 2 1 ) = 7 ( 47 1 ) = 322 \begin{aligned} a^2+b^2 & = (a+b)^2 - 2ab \\ a^3+b^3 & = (a+b)(a^2+b^2 - ab) \\ \Rightarrow x^2+\frac{1}{x^2} & = \left(x+\frac{1}{x} \right)^2 - 2x\left(\frac{1}{x} \right) = 7^2 - 2 = 47 \\ \Rightarrow x^3 + \frac{1}{x^3} & = \left(x+\frac{1}{x}\right) \left(x^2+\frac{1}{x^2} - 1 \right) = 7(47-1) = \boxed{322} \end{aligned}

Can expand directly right? I mean no need square

Wendy Natuibs - 6 years ago

we can do it more simply by aplying formula of cube

Anshu Rai - 6 years ago

Another approach is to use the identity ( x + y ) 3 = x 3 + y 3 + 3 x y ( x + y ) (x+y)^3=x^3+y^3+3xy(x+y) .

( x + 1 x ) 3 = x 3 + 1 x 3 + 3 x 1 x ( x + 1 x ) x 3 + 1 x 3 = 7 3 3 × 1 × 7 = 343 21 = 322 \left(x+\frac 1x\right)^3=x^3+\frac 1{x^3}+3\cdot x\cdot \frac 1x\left(x+\frac 1x\right)\\ \implies x^3+\frac 1{x^3}=7^3-3\times 1\times 7=343-21=\boxed{322}

Prasun Biswas - 6 years ago

x + 1 x = 7 x 3 + ( 1 x ) 3 = ? l e t x = a a n d 1 x = b s o ( a + b ) 3 = a 3 + 3 a 2 b + 3 a b 2 + b 3 ( a + b ) 3 = a 3 + b 3 + 3 ( a 2 b + a b 2 ) ( x + 1 x ) 3 = x 3 + ( 1 x ) 3 + 3 ( x 2 1 x + x ( 1 x ) 2 ) ( 7 ) 3 = x 3 + ( 1 x ) 3 + 3 ( ( x + 1 x ) ) ( 7 ) 3 = x 3 + ( 1 x ) 3 + 3 ( 7 ) ( 7 ) 3 3 ( 7 ) = x 3 + ( 1 x ) 3 343 21 = x 3 + ( 1 x ) 3 x 3 + ( 1 x ) 3 = 322 x + \frac 1x = 7\\{x}^3 + \left(\frac {1}{x}\right)^3 = ?\\let\;x = a\;and\;\frac {1}{x} = b\\so\;(a + b)^3 = a^3 + 3a^2 b + 3ab^2 + b^3\\(a + b)^3 = a^3 + b^3 + 3(a^2 b + ab^2)\\ \left(x + \frac {1}{x}\right)^3 = x^3 + \left(\frac {1}{x}\right)^3 + 3(x^2 \frac 1x + x \left(\frac {1}{x}\right)^2)\\(7)^3 = x^3 + \left(\frac {1}{x}\right)^3 + 3((x + \frac 1x ))\\(7)^3 = x^3 + \left(\frac {1}{x}\right)^3 + 3(7)\\ (7)^3 - 3(7) = x^3 + \left(\frac {1}{x}\right)^3\\ 343 - 21 = x^3 + \left(\frac {1}{x}\right)^3\\x^3 + \left(\frac {1}{x}\right)^3 = 322

Anish Harsha
Jun 11, 2015

First, ( x + 1/ x )^3 = x^3 + 1/ x^3 * x * 1/x ( x+ 1/x ),
( x + 1/ x )^3 = x^3 + 1/ x^3 + 3( x + 1/x ),

Putting x + 1/x = 7, we get,
7^3 = x^3 + 1/ x^3 + 3*7,
343 = x^3 + 1/x ^3 + 21,
= x^3 + 1/x ^3 = 343 -21,
x^3 + 1/x^ 3 = 322.



So, the answer is 322.

Share my post and like too if you like it.

Omg thats so deep haha

LJ Nambio - 6 years ago
Majed Musleh
Jun 12, 2015

( x + 1 x ) 2 = 7 2 x 2 + 2 x x + 1 x 2 = 49 = > x 2 + 1 x 2 = 47........ ( 1 ) (x+\frac{1}{x})^{2}=7^{2} \\ x^{2}+2\frac{x}{x}+\frac{1}{x^{2}}=49 \\ =>x^{2}+\frac{1}{x^{2}}=47........(1)

x 3 + ( 1 x ) 3 = ( x + 1 x ) ( x 2 + 1 x 2 x x ) = ( 7 ) ( 47 1 ) = 322 x^{3}+(\frac{1}{x})^{3}=(x+\frac{1}{x})(x^{2}+\frac{1}{x^{2}}-\frac{x}{x}) \\ =(7)(47-1)=\boxed{322}

Sparsh Chaudhri
Jun 12, 2015

x + 1/x = 7

x^3 + 1/x^3 = x^3 + 1/x^3 + 3(x + 1/x)

= x^3 + 1/x^3 + 3(7)

7^3 = x^3 + 1/x^3 + 21

x^3 + 1/x^3 = 343 - 21

= 322

[extra spaces for clarification]

Yes I did like you too. The rest so complicated.

Wendy Natuibs - 6 years ago
Fidel R.
Jun 12, 2015

x + 1 x = 7 x + \frac{1}{x} = 7 ( x + 1 x ) 3 = 7 3 (x + \frac{1}{x} )^{3} = 7^{3} ( x + 1 x ) 2 ( x + 1 x ) = 343 (x + \frac{1}{x} )^{2}(x + \frac{1}{x}) = 343 ( x 2 + 2 + 1 x 2 ) ( x + 1 x ) = 343 (x^{2} + 2 + \frac{1}{x^{2}})(x + \frac{1}{x}) = 343 x ( x 2 + 2 + 1 x 2 ) + 1 x ( x 2 + 2 + 1 x 2 ) = 343 x(x^{2} + 2 + \frac{1}{x^{2}}) + \frac{1}{x}(x^{2} + 2 + \frac{1}{x^{2}}) = 343 x 3 + 2 x + 1 x + x + 2 x + 1 x 3 = 343 x^{3} + 2x + \frac{1}{x} + x + \frac{2}{x} + \frac{1}{x^{3}} = 343 x 3 + 3 x + 3 x + 1 x 3 = 343 x^{3} + 3x + \frac{3}{x} + \frac{1}{x^{3}} = 343 x 3 + 3 ( x + 1 x ) + 1 x 3 = 343 x^{3} + 3 (x + \frac{1}{x} ) + \frac{1}{x^{3}} = 343 x 3 + 3 ( 7 ) + 1 x 3 = 343 x^{3} + 3 (7 ) + \frac{1}{x^{3}} = 343 x 3 + 21 + 1 x 3 = 343 x^{3} + 21 + \frac{1}{x^{3}} = 343 x 3 + 1 x 3 = 322 \boxed{x^{3} + \frac{1}{x^{3}} = 322}

Shashank Rustagi
Jun 12, 2015

(x + 1/x )^3 = 343 also it is equal to x^3 + 1/x^3 + 3 x (1/x)(x+ 1/x) by substituting the values x^3 + 1/x^3 + 21 = 343 it implies that x^3 + 1/x^3 = 343-21 = 322

a 3 + b 3 = ( a + b ) 3 3 a b ( a + b ) a^3 + b^3 = (a+b)^3 -3ab(a+b) Substitute a = x , b = 1 x a = x, b =\frac {1}{x} We get, x 3 + 1 x 3 = ( x + 1 x ) 3 3 ( x + 1 x ) x^3 + \frac{1}{x^3} = (x +\frac{1}{x})^3 - 3(x + \frac {1}{x}) = ( 7 ) 3 3 ( 7 ) = 343 21 = 322 = (7)^3 - 3(7) = 343 - 21 = 322

Tootie Frootie
Jun 15, 2015

Multiply the first equation by x to get a quadratic solve for x. x=6.8541. Place the value of x into lower equation =322

Wendy Natuibs
Jun 12, 2015

Cube it minus 3 times itself you get answer.

Joseph Li
Jun 12, 2015

x+1/x=7
(x+1/x)^2=49
x^2+1/x^2=47
(x^2+1/x^2)(x+1/x)=(47)(7)
x^3+1/x^3+x+1/x=329
x^3+1/x^3=322




While doing this, I also noticed that you could just do whatever x+1/x is equal to (in this case 7) and put it to the 3rd power because that's the highest degree of what you're trying to find (from x^3+1/x^3). Then you can subtract the highest degree times what x+1/x is equal to from it. So in other words, 7^3 - (3)(7). I don't think it works for all of these types of problems though, but I tried some that had 3 as the highest degree of what you're asked to find, and it seemed to work.

Woody Superman
Jun 12, 2015

x+ 1/x = 7 => (x + 1/x)^2 = 49 => x^2 + 2 + 1/x^2 = 49 => x^2 + 1/x^2 = 47

x^3 + 1/x^3 = (x + 1/x)(x^2 - 1 + 1/x^2) = 7 * (47 -1) = 7 * 46 = 322

(x+1/x)^3-3.x.1/x+(x+1/x)

Ajantu Islam - 6 years ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...